Conservative treatment of complete dislocation of the thumb metacarpal in a hypermobile patient - Deniz Aydin; Baris Polat (Archives of Trauma Research, 2018)
Simultaneous dislocation of the thumb carpometacarpal and metacarpophalangeal joints is an uncommon injury. Stability is the most important factor in the decision of treatment in these rare injuries. The treatment methods range from closed reduction and maintaining reduction with cast or percutaneous k-wires to complex reconstruction surgeries. In this paper, a case of 28-year-old female with complete dislocation of the left thumb metacarpal has been reported. She was treated with closed reduction and cast immobilization with excellent result. Treatment decision should be based on postreduction stability in complete dislocation of thumb metacarpal; cast immobilization is a management option in case of stable reduction.